GESTION DEL MARKETING POLÍTICO DIGITAL Y SU INFLUENCIA EN LA PARTICIPACION ELECTORAL CIUDADANA EN LA PARROQUIA SAN CRISTOBAL DEL CANTON QUEVEDO, AÑO 2024. - Ibarra Cedeño, Erika Salome (2024)
This study focuses on analyzing how digital political marketing is influencing the way in which the citizens of Quevedo, Ecuador, and how they participate in elections, the argument that exists is the increasingly sophisticated evolution in which political campaigns are managed. in which there is an interconnection between politicians and voters. Digital platforms play a crucial role in forming voter preferences and influencing voter turnout, with targeted advertising allowing campaigns to tailor their messages to specific demographic segments. The lack of digital literacy among older voters creates a digital divide. Political marketing is a discipline that applies the tools and strategies of commercial marketing to the political sphere with the aim of influencing public opinion and is based on research into the needs and preferences of the electorate. Market research plays a fundamental role in understanding the trends and preferences of the electorate, and the media, both personal and impersonal, are key tools for transmitting political messages. Political marketing professionals play a crucial role in the design and implementation of these strategies, using various techniques and tools to achieve success in an increasingly competitive political environment.